Time-delayed layer-based piezoelectric transducer for unidirectional excitation and reception of SH guided wave. (15th June 2023) - Du, Yuehao; Cai, Jiangcheng; Kan, Qianhua; Zhang, Qinghua; Wang, Ping; Miao, Hongchen; Kang, Guozheng
Graphical abstract: Highlights: A piezoelectric transducer is proposed for unidirectionally generating and receiving pure SH0 wave over a wide frequency range. In both unidirectional excitation and reception, no extra time delay is required for the proposed transducer. Theoretical predictions, simulations and experiments validate the excellent unidirectionality of the transducer. Pure SH0 wave with an experimentally measured unidirectionality of about 22 dB is obtained. Abstract: Unidirectional excitation of a single-mode guided wave (GW) is of great significance in GW-based structural health monitoring (SHM) and nondestructive testing (NDT). Currently, very few transducers are capable of generating unidirectional propagation GW in plate-like structures, so such a goal is usually achieved by using phased array transducers, which are relatively expensive and only work within a narrow frequency range. In this work, a time-delayed layer-based piezoelectric transducer (TDLBPT) is developed for unidirectionally generating and receiving pure SH0 wave (zero-order shear horizontal wave). The TDLBPT consists of a time-delayed layer and two rectangular thickness-shear (d15 ) mode piezoelectric wafers. The time-delayed layer component is designed for achieving the phase gradient over a wide range of frequencies, so in both unidirectional excitation and reception, no extra time delay is required for the proposed TDLBPT. An analytic model is proposed to predict the SH0 wavefields generated by the TDLBPT, which can provide guidelines for designing the TDLBPT. Finite element (FE) simulations and experiments are performed to examine the performance of the developed TDLBPT. Both simulated and experimental results show that the TDLBPT can generate pure SH0 wave and focus the wave energy along a given direction in a plate over a wide range of frequencies. Moreover, the reception performance of the TDLBPT also shows excellent unidirectionality. Due to the excellent performance and easy fabrication, the proposed TDLBPT will be very useful in unidirectional excitation and reception of SH0 wave in SHM and NDT.